2020
DOI: 10.1002/poc.4075
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of excited state charge and proton transfer mechanism for the novel 10‐methyl‐indolo[2,3‐a]‐indolo[2,3‐a′]acridone molecule

Abstract: A novel acridone derivative, 10‐methyl‐indolo[2,3‐a]‐indolo[2,3‐a′]acridone (13), was reported by Fang and coworkers [J. Org. Chem. 2019, 84, 3832] in a previous paper. Spectroscopic studies on excited‐state intramolecular proton transfer (ESIPT) of 13 were mentioned, while the mechanism of ESIPT for 13 is deficiency. In this present work, based on the time dependent density functional theory (TDDFT), we investigated the ESIPT mechanism of 13 theoretically. The primary bond lengths, bond angles and the infrare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The constructing potential energy curve of S 0 state is based on the shortening of F and Si bond length from 5.00 to 1.40 Å with fixing the step of 0.10 Å, which is a good manner to deal with the studies of fluorescence sensor. [ 37–45 ] It can be seen clearly that the formation of the intermediate (i.e., the complex between TBDI and fluoride anion) is endergonic about 7.613 kcal/mol in the ground state. And the fluoride anion interacts with TBDI sensor via hydrogen bonding interaction in the intermediate complex.…”
Section: Resultsmentioning
confidence: 99%
“…The constructing potential energy curve of S 0 state is based on the shortening of F and Si bond length from 5.00 to 1.40 Å with fixing the step of 0.10 Å, which is a good manner to deal with the studies of fluorescence sensor. [ 37–45 ] It can be seen clearly that the formation of the intermediate (i.e., the complex between TBDI and fluoride anion) is endergonic about 7.613 kcal/mol in the ground state. And the fluoride anion interacts with TBDI sensor via hydrogen bonding interaction in the intermediate complex.…”
Section: Resultsmentioning
confidence: 99%
“…Later, the dual fluorescence of the indole‐fused acridone was spectroscopically studied, showing keto and enol emissions at about 450 and 650 nm, respectively [69]. A theoretical investigation of the same system by TD‐DFT was reported by Yang et al one year later [70]. By studying the potential energy curves (PECs) along the NH coordinate, the authors concluded that the intramolecular PT (from NH indole to CO of the acridone) occurs at the excited state with a barrier of 6.7 kcal/mol.…”
Section: Introductionmentioning
confidence: 99%